Building trust through public service co-production. Issue 7 (12th October 2015) - Fledderus, Joost
Abstract : Purpose: – Co-production of public service delivery is believed to foster trust among users, but little empirical work is devoted to this assumption. Public sector organizations have therefore little knowledge about the conditions that determine whether co-production leads to trust. The paper aims to discuss these issues. Design/methodology/approach: – A longitudinal mixed method is used, following participants of a co-produced activation programme over time ( n =60). Quantitative methods are employed to investigate changes in trust levels, whereas qualitative methods are used to explain these changes and explore conditions for trust-building. Findings: – After a half year, trust in the service provider, trust in local government and generalized trust decreased significantly among co-producing participants. Particularly, a decrease in trust in fellow participants strongly related to decreases in trust in the service provider and generalized trust. Qualitative evidence indicate that motivation during the co-production decreased, as well as personal control. Organizational support and user commitment show to be important conditions for building trust. Research limitations/implications: – The study draws upon a small sample, limiting possibilities for statistical analysis. Also, comparison with other types of service delivery is required to safely assign the effects to co-production. Originality/value: – Longitudinal studies on co-production are rarely performed. Additionally, the findings indicate a more critical approach to the effects of co-production, which are often assumed to be positive for the public sector and citizens.